Evaluasi Pembelajaran Berbasis Digital di Sekolah Dasar: Studi Deskriptif Kualitatif Berdasarkan Observasi Lapangan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to describe the implementation of digital-based learning evaluation in elementary schools, including the types of media, methods of implementation, advantages, obstacles, and its relevance to evaluation theory. The research method used a descriptive qualitative approach with non-participant observation, semi-structured interviews, and documentation at five elementary schools in Jakarta and Bandung, namely Narada School, Bakti Mulya 400, Cendekia Leadership School, Binekas, and Bandung Alliance Intercultural School. The results showed variations in the implementation of digital evaluation, ranging from project-based authentic assessment and teacher observation to integrated digital systems using LMS, Google Classroom, Quizizz, and Kahoot. Digital evaluation was found to improve efficiency, motivation, student engagement, transparency, and documentation of learning outcomes. The challenges faced included technological readiness, digital literacy, technical glitches, student distractions, and the risk of cheating. These findings are in line with the theories of authentic assessment, constructivism, and formative and summative evaluation. The research conclusion emphasizes the importance of developing teachers' digital competencies, strengthening school technology infrastructure, and adjusting evaluation methods to be able to optimally assess students' cognitive, affective, and psychomotor aspects, thereby supporting the improvement of learning quality in elementary schools.